Modifikasi Labu Ekstraksi untuk Menghemat Penggunaan Pelarut Lemak dan Efisiensi Ekstraksi - Subandi Subandi; Sukiyadi Sukiyadi (Jurnal Ilmiah Teknik Pertanian - TekTan, 2019)
Limitations costs of laboratory, project business student and research using equipment soxhlet is a problem that often arise and require solutions to overcome them, one way to overcome this problem is to save the use of material without reducing the quality of the results of lab activities and research implemented. Tool Extraction of fat (soxhlet fat extraction unit) is a set of tools to perform the extraction of the fat/oil in a wide variety of materials in the form of solids, the working principle of this device is to extract the fat/oil in the ingredients with a fat solvent that is non-polar, the process of extraction takes place at subsequent extraction flask extraction results flow and accommodated in the cup of fat. Volume 150 ml cup of fat. must be filled by a grease solvent, while the fat solvent prices more expensive, so the availability of fat solvent in a chemical warehouse is relatively limited so we need innovative ways to overcome these problems. Modification of extraction flask for save of fat solvent and efficiency of extraction is an effort to conserve fat solvent by adding material to the flask extraction as an oppressor of materials that are extracted while reducing the volume of the flask extraction, thus the suppression of material extracted then extraction is efficient and the volume of solvent needed to extract the fat/oil over 24.882 percent saving.Keywords: soxhlet, solvent-fat/oil, efficiency